(untitled) (Development Service Industry Management, 2025)
The article examines the effectiveness of using digital communication tools in managing remote project teams in the context of digital transformation, globalized competition, and the spread of remote and hybrid forms of employment. It identifies key categories of tools that enable virtual teams to function, including systems for written and oral communication, task and project management platforms, document collaboration services, and knowledge bases. It has been found that digital tools contribute to the continuity of work processes and increase transparency and coordination, but their use is accompanied by a number of challenges, including information overload, technical inequality, asynchronous interaction, cyber risks, and psychological exhaustion of employees. Based on an analysis of scientific sources and practical experience, a set of managerial, technical, and socio-psychological measures has been proposed to minimize these risks: regulation of communication processes, development of digital literacy, application of cyber security measures, combination of synchronous and asynchronous interaction models, and support for employee mental health. It is concluded that digital tools alone do not guarantee an increase in the effectiveness of remote teams—their potential is realized only when technological solutions are harmoniously combined with management approaches and organizational culture. The results obtained can be used to improve project team management practices and develop strategies to increase the competitiveness of organizations in the digital age.